Recent developments and applications on high-performance cast magnesium rare-earth alloys - Wu, Guohua; Wang, Cunlong; Sun, Ming; Ding, Wenjiang (Journal of magnesium and alloys, 2021)
During the past decades, with the increasing demands in lightweight structural materials, Mg alloys with low density and high performance have been extensively investigated and partly applied in some industries. Especially when rare earth (RE) elements are added as major alloying elements to Mg alloys, the alloy strength and creep resistance are greatly improved, which have promoted several series of Mg-RE alloys. This paper reviews the progress and developments of high-performance Mg-RE alloys in recent years with emphasis on cast alloys. The main contents include the alloy design, melt purification, grain refinement, castability, novel liquid casting and semisolid forming approaches, and the industrial applications or trials made of Mg-RE alloys. The review will provide insights for future developments of new alloys, techniques and applications of Mg alloys.